Aggregate fluctuations and the role of trade credit - Lin Shao (Bank of Canada, 2017)
In an economy where production takes place in multiple stages and is subject to financial frictions, how firms finance intermediate inputs matters for aggregate outcomes. This paper focuses on trade credit - the lending and borrowing of input goods between firms - and quantifies its aggregate impacts during the Great Recession. Motivated by empirical evidence, our model shows how trade credit alleviates financial frictions through a process of credit redistribution and creation, thus leading to a higher output level in the steady state. However, in the face of financial market distress, suppliers cut back trade credit lending, further tightening their customers' borrowing constraint. The decline in economic activities following financial shocks is in turn amplified by disruptions in trade credit. Our model simulation suggests that the drop in trade credit during the Great Recession can account for almost one-fourth of the observed decline in output.
Keywords: E32; E44; E51; 330; Business fluctuations and cycles; Credit and credit aggregates; Firmdynamics